Eco Print Training to Increase the Income of Women Leaders of the Pagah Branch of ‘Aisyiyah Through Hijab, Pashmina, Tablecloth, and Bag Products - pater, dewilusiana; Nugroho, aji brahma; muhtar; agung nilogiri (Journal Of Humanities Community Empowerment, 2026)
Eco Print Training is a community service program motivated to improve women's economic independence through productive activities based on local potential. Urgency of this program stems from women's limited access to marketable creative skills and opportunities for low-capital businesses with high market prospects. Eco print was chosen because it is environmentally friendly, easily found natural materials, and produces aesthetic products that increasing demand in the fashion and home decoration sectors. Objectives of this activity are to improve the technical skills in producing quality eco print products, strengthen their entrepreneurial skills, and open up opportunities increase family income. Program aims to encourage the growth of entrepreneurship based on the environment and local potential. The implementation method includes practice-based training covering an introduction to the concept of eco-printing, techniques for selecting leaves and flowers, the mordanting process, motif composition, steaming techniques, and the finishing stages to create a sale-ready product. Participants also receive entrepreneurial assistance, including training in branding, packaging, digital marketing strategies, and sales simulations. The targeted outcomes of the activity include eco-print products (hijabs, pashminas, tablecloths, chair cushions, and bags), eco-print training modules, activity videos, improved participant skills, increased income, published scientific articles, and online media coverage of the activity